Antimicrobial capacity of photodynamic therapy on apical debris of root canals instrumented with a reciprocating system - Santos, Aline Silva dos; Martin, Alexandre Sigrist de; Fontana, Carlos Eduardo; Bueno, Carlos Eduardo da Silveira; Pinheiro, Sérgio Luiz (International Journal of Advanced Engineering Research and Science, 2020)
Purpose: The aim of this study was to evaluate the antimicrobial action of photodynamic therapy (PDT) on apically extruded debris after root canal system (RCS) instrumentation using WaveOne Gold (WOG) files. Methods: Thirty mesial roots from permanent mandibular molars were selected. The mesiobuccal canal of each root was contaminated with standard-strain Enterococcus faecalis ATCC29212 for 21 days and randomly divided into two groups (n=15): WOG, canals instrumented with WOG file; WOG + PDT, photodynamic therapy performed after instrumentation with WOG. The parameters used for PDT were: low power laser with a wavelength of 660 μm, power of 100 mW, energy of 9.6 J, irradiation time of 96 seconds, and fiber diameter of 600 μm. E. faecalis samples, as well as apical debris, were collected before and after each procedure. Descriptive analysis was performed and the Kruskal-Wallis (Dunn) nonparametric test was applied, with a significance level of 5%. Results: Significant reductions in E. faecalis were observed after instrumentation in both groups (p<0.05). Regarding debris, microbial reduction occurred only in the group in which PDT was performed after instrumentation (p<0.05). Conclusion: The combination of PDT and reciprocating instrumentation effectively reduced Enterococcus faecalis burden in apically extruded debris.